Successful collection of peripheral blood progenitor cells in patients with acute myeloid leukaemia following early consolidation therapy with granulocyte colony-stimulating factor-supported high-dose cytarabine and mitoxantrone - Schlenk, Richard Friedrich; Döhner, Hartmut; Pförsich, Margit; Benner, Axel; Döhner, Konstanze; Hartmann, F.; Fischer, J. Th.; Weber, W.; Gunzer, U.; Pralle, H.; Haas, Rainer (British journal of haematology, 1997)
We evaluated the feasibility of collecting peripheral blood progenitor cells (PBPC) in patients with acute myeloid leukaemia (AML) following two cycles of induction chemotherapy with idarubicin, cytarabine and etoposide (ICE), and one cycle of consolidation therapy with high-dose cytarabine and mitoxantrone (HAM). Thirty-six patients of the multicentre treatment trial AML HD93 were enrolled in this study, and a sufficient number of PBPC was harvested in 30 (83%). Individual peak concentrations of CD34+ cells in the blood varied (range 13.1-291.5/μl; median 20.0/μl). To reach the target quantity of 2.5 × 106 CD34+ cells/kg, between one and six (median two) leukaphereses (LP) were performed. The LP products contained between 0.2 × 106 and 18.9 × 106 CD34+cells/kg (median 1.2 × 106/kg). Multivariate analysis showed that the white blood cell count prior to HAM and the time interval from the start of HAM therapy to reach an unsupported platelet count > 20 × 109/l were predictive for the peak value of CD34+ cells in the blood during the G-CSF stimulated haematological recovery. In 16 patients an intraindividual comparison was made between bone marrow (BM) and PBPC grafts. Compared to BM grafts, PBPC grafts contained 14-fold more MNC, 5-fold more CD34+ cells and 36-fold more CFU-GM. A CD34+ subset analysis showed that blood-derived CD34+ cells had a more immature phenotype as indicated by a lower mean fluorescence intensity for HLA-DR and CD38. In addition, the proportion of CD34+/Thy-1+ cells tended to be greater in the PBPC grafts. The data indicate that sufficient PBPC can be collected in the majority of patients with AML following intensive double induction and first consolidation therapy with high-dose cytarabine and mitoxantrone.
Gesehen am 31.10.2024